Genome-Wide Identification and Functional Analysis of Lysine Histidine Transporter (LHT) Gene Families in Maize - Md. Golam Rabby; Md. Munnaf Hossen; Md. Mostafa Kamal; Md. Numan Islam (Genetics Research)
Amino acid transporters (AATs) are essential membrane proteins that transfer amino acids across cells. They are necessary for plant growth and development. The lysine histidine transporter (LHT) gene family in maize (Zea mays) has not yet been characterized. According to sequence composition and phylogenetic placement, this study found 15 LHT genes in the maize genome. The ZmLHT genes are scattered across the plasma membrane. The study also analyzed the evolutionary relationships, gene structures, conserved motifs, 3D protein structure, a transmembrane domain, and gene expression of the 15 LHT genes in maize. Comprehensive analyses of ZmLHT gene expression profiles revealed distinct expression patterns in maize LHT genes in various tissues. This study’s extensive data will serve as a foundation for future ZmLHT gene family research. This study might make easier to understand how LHT genes work in maize and other crops.